A Single Dose of BNT162b2 Messenger RNA Vaccine Induces Airway Immunity in Severe Acute Respiratory Syndrome Coronavirus 2 Naive and Recovered Coronavirus Disease 2019 Subjects. (17th May 2022) - Martinuzzi, Emanuela; Benzaquen, Jonathan; Guerin, Olivier; Leroy, Sylvie; Simon, Thomas; Ilie, Marius; Hofman, Véronique; Allegra, Maryline; Tanga, Virginie; Michel, Emeline; Boutros, Jacques; Maniel, Charlotte; et al.
Abstract: Background: Mucosal antibodies can prevent virus entry and replication in mucosal epithelial cells and therefore virus shedding. Parenteral booster injection of a vaccine against a mucosal pathogen promotes stronger mucosal immune responses following prior mucosal infection compared with injections of a parenteral vaccine in a mucosally naive subject. We investigated whether this was also the case for the BNT162b2 coronavirus disease 2019 (COVID-19) messenger RNA vaccine. Methods: Twenty recovered COVID-19 subjects (RCSs) and 23 severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–naive subjects were vaccinated with, respectively, 1 and 2 doses of the BNT162b2 COVID-19 vaccine. Nasal epithelial lining fluid (NELF) and plasma were collected before and after vaccination and assessed for immunoglobulin G (IgG) and IgA antibody levels to Spike and for their ability to neutralize binding of Spike to angiotensin-converting enzyme-2 receptor. Blood was analyzed 1 week after vaccination for the number of Spike-specific antibody-secreting cells (ASCs) with a mucosal tropism. Results: All RCSs had both nasal and blood SARS-CoV-2–specific antibodies at least 90 days after initial diagnosis. In RCSs, a single dose of vaccine amplified preexisting Spike-specific IgG and IgA antibody responses in both NELF and blood against both vaccine homologous and variant strains, including Delta. These responses were associated with Spike-specific IgG and IgA ASCs with a mucosal tropism in blood. Nasal IgA and IgG antibody responses were lower in magnitude in SARS-CoV-2–naive subjects after 2 vaccine doses compared with RCSs after 1 dose. Conclusions: Mucosal immune response to the SARS-CoV-2 Spike protein is higher in RCSs after a single vaccine dose compared with SARS-CoV-2–naive subjects after 2 doses. Abstract : Messenger RNA vaccines induce a specific immunoglobulin A (IgA) and IgG response in nasal epithelial lining fluid of severe acute respiratory syndrome coronavirus 2–naive subjects and have a booster effect in recovered coronavirus disease 2019 subjects.